If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -11 = -32 + 4x Reorder the terms: -11 + 7x = -32 + 4x Solving -11 + 7x = -32 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -11 + 7x + -4x = -32 + 4x + -4x Combine like terms: 7x + -4x = 3x -11 + 3x = -32 + 4x + -4x Combine like terms: 4x + -4x = 0 -11 + 3x = -32 + 0 -11 + 3x = -32 Add '11' to each side of the equation. -11 + 11 + 3x = -32 + 11 Combine like terms: -11 + 11 = 0 0 + 3x = -32 + 11 3x = -32 + 11 Combine like terms: -32 + 11 = -21 3x = -21 Divide each side by '3'. x = -7 Simplifying x = -7
| 6x^3+x+1= | | 11x+3=7x+2(5+2x) | | 3x-10=-6+x | | 8+3e^7c=23 | | (1/4)(x-28)=(3/4) | | 0.8888888888888888888888-1/2 | | (X^3)/(x-1)^4=1000 | | 2(3y+1)=8 | | 3y=18x+14 | | r^3+21r+20=0 | | X-2+x-2+x-2= | | 8u-10=77-21u | | 0.25x-3.8y= | | (4x)-(3/x) | | 131=12x+11 | | 10x+20=5x-100 | | 3x^2-x-100=0 | | 9=3j-3 | | 40=14y-9y | | C-x=y | | 5x-5=14x-16 | | 3p+49= | | 3x+6=11y+4 | | 6x-8=5x-4 | | -42=-1.2x | | -7b=-91 | | 3y=-4+15 | | -6y-3y+6y+6x= | | ln(2x+5)=7 | | 1/2x2/5x3/4= | | 3/5(2/3) | | 6-3(x-2)+12=-2x+24-x |